Kisspeptin-neuron control of LH pulsatility and ovulation - Stevenson, Harvey; Bartram, Samuel; Charalambides, Mikaela Maria; Murthy, Sruthi; Petitt, Theo; Pradeep, Anjali; Vineall, Owen; Abaraonye, Ikenna; Lancaster, Amelia; Koysombat, Kanyada; Patel, Bijal; Abbara, Ali (Frontiers in Endocrinology, 2022)
Feedback from oestradiol (E2) plays a critical role in the regulation of major events in the physiological menstrual cycle including the release of gonadotrophins to stimulate follicular growth, and the mid-cycle luteinising hormone (LH) surge that leads to ovulation. E2 predominantly exerts its action via oestrogen receptor-alpha (ERα), however, as gonadotrophin releasing hormone (GnRH) neurons lack ERα, E2-feedback is posited to be indirectly mediated via upstream neurons. Kisspeptin (KP) is a neuropeptide expressed in hypothalamic KP-neurons that control GnRH secretion and plays a key role in the central mechanism regulating the hypothalamic-pituitary-gonadal (HPG) axis. In the rodent arcuate (ARC) nucleus, KP is co-expressed with Neurokinin B and Dynorphin; and thus, these neurons are termed ‘Kisspeptin-Neurokinin B-Dynorphin’ (KNDy) neurons. ARC KP-neurons function as the ‘GnRH pulse generator’ to regulate GnRH pulsatility, as well as mediating negative feedback from E2. A second KP neuronal population is present in the rostral periventricular area of the third ventricle (RP3V), which includes anteroventral periventricular (AVPV) nucleus and preoptic area neurons. These RP3V KP-neurons mediate positive feedback to induce the mid-cycle luteinising hormone (LH) surge and subsequent ovulation. Here, we describe the role of KP-neurons in these two regions in mediating this differential feedback from oestrogens. We conclude by considering reproductive diseases for which exploitation of these mechanisms could yield future therapies.